Valorizing alum sludge waste augmented ferrite as a sustainable magnetic pathway for treating Indigo carmine effluent - Ahmed H. Mangood; Eman Sh. Salama; Ibrahim E. T. El-Sayed; Mai K. Fouad; Maha A. Tony (Scientific Reports)
Abstract One of the guiding sustainability principles is centered on mitigating the waste streams through the industrial ecology manner. On this regard, this research examines the conversion of dewatered alum sludge (AS) waste derived from water-works plants to be and innovative, magnetic and inexpensive nanoadsorbent. Alum sludge (AS) is calcined at 400 °C and mixed with zinc ferrite (F-Zn) that is prepared by simple co-precipitation route and signified with its high chemical stability, harmfulness as well as good magnetic properties that makes them a candidate as reusable adsorbent. The composite is mixed at varied proportions and labeled as AS400 (F-Zn/AS400 (1:1), F-Zn/AS400 (2:1) and F-Zn/AS400 (1:2). Such materials are thereby checked for their composition, structure and physical–chemical characterized through X-ray diffraction, Fourier transform infrared spectroscopy, transmission electron microscopy, scanning electron microscopy, Energy dispersive X-ray Spectroscopy, vibrating sample magnetometer, and Brunauer–Emmett–Teller. Then, the composites are applied for anionic dye so-called Indigo carmine (IC) adsorption through a comparative manner. The operating parameters are examined and the experimental results revealed that the isotherm time for all adsorbents is corresponding to 2 h using 0.5 g/L of the applied materials dose. Also, the aqueous medium pH is checked and the point of zero charge is evaluated and confirmed the IC removal was successful in an acidic medium (pH 2.0). The temperature influence verified the process is exothermic in nature. Kinetic modeling is evaluated and the results are well fitted with the pseudo-second order model. Various isotherm models are applied and the data is fitting the Langmuir isotherm model. The presence of ferrite improves the AS400 capacity from to 12.57 to 29.42 mg/g.